Fundamentals of materials science and engineering an integrated approach - Callister, William D.; Rethwisch, David G. (John Wiley & Sons, 2016)
Fundamentals of Materials Science and Engineering: An Integrated Approach, 5th Edition SI Version takes an integrated approach to the sequence of topics one specific structure, characteristic, or property type is covered in turn for all three basic material types: metals, ceramics, and polymeric materials.